Time course transcriptomic profiling suggests Crp/Fnr transcriptional regulation of nosZ gene in a N2O-reducing thermophile - Jiro Tsuchiya; Sayaka Mino; Fuki Fujiwara; Nao Okuma; Yasunori Ichihashi; Robert M. Morris; Brook L. Nunn; Emma Timmins-Schiffman; Tomoo Sawabe (iScience)
Summary: Nitrosophilus labii HRV44T is a thermophilic chemolithoautotroph possessing clade II type nitrous oxide (N2O) reductase (NosZ) that has an outstanding activity in reducing N2O to dinitrogen gas. Here, we attempt to understand molecular responses of HRV44T to N2O. Time course transcriptome and proteomic mass spectrometry analyses under anaerobic conditions revealed that most of transcripts and peptides related to denitrification were constitutively detected, even in the absence of any nitrogen oxides as electron acceptors. Gene expressions involved in electron transport to NosZ were upregulated within 3 h in response to N2O, rather than upregulation of nos genes. Two genes encoding Crp/Fnr transcriptional regulators observed upstream of nap and nor gene clusters had significant negative correlations with nosZ expression. Statistical path analysis further inferred a significant causal relationship between the gene expression of nosZ and that of one Crp/Fnr regulators. Our findings contribute to understanding the transcriptional regulation in clade II type N2O-reducers.